Ergonomic Risk Assessment of Manual Material Handling in a Logistic Warehouse - Mohamad Rani, Syahmina Izzati; Amir Haziq Abdul Razak, (Progress in Engineering Application and Technology, 2026)
Manual Material Handling (MMH) is a critical component of logistics operations, yet it remains a primary driver of work-related musculoskeletal disorders (WMSDs) due to high physical demands. This study investigated the ergonomic risk factors associated with MMH tasks at the Ninja Van Malaysia central warehouse. The primary objectives were to identify the prevalence of musculoskeletal discomfort among workers, classify ergonomic risk levels using the Department of Occupational Safety and Health (DOSH) Initial Ergonomic Risk Assessment (IERA) Guidelines (2017), and propose feasible control measures based on the findings. A mixed-methods research design was employed, utilizing the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) for subjective discomfort reporting and direct site observations for task analysis. A purposive sample of 40 experienced workers was assessed. Results from the CMDQ revealed a high prevalence of discomfort, particularly in the lower extremities, with 60% of respondents reporting right-knee pain and 55% reporting right-foot discomfort. Additionally, significant strain was noted in the neck (45%) and upper back (37.5%). The IERA identified several critical risk factors: 70% of workers were exposed to prolonged static standing, 40% performed frequent reaching above shoulder height, and 35% engaged in torso twisting during lifting tasks. Environmental constraints, including clutter (57.5%) and limited workspace (45%), further exacerbated awkward postures. Furthermore, 72.5% of workers operated without mechanical assistance, and 60% reported a lack of formal ergonomic training. Based on these findings, key MMH tasks were classified as Medium to High Risk, necessitating immediate intervention. Proposed control measures include engineering solutions such as height-adjustable conveyors and anti-fatigue matting, alongside administrative strategies like formal job rotation and the implementation of a 5S housekeeping system. This research provides a proactive framework for warehouse managers to enhance worker safety, reduce injury-related absenteeism, and improve overall operational efficiency in the logistics sector.